Reinforced pavement above trench under urban traffic load: case study and finite element (FE) analysis - Kazemian, Sina; Barghchi, Maassoumeh; Prasad, Arun; Maydi, Hossein; Kim Huat, Bujang (Academic Journals, 2010)
Every year, 2000 km length of trench is being excavated through an existing pavement in Iran for installing urban waste water pipelines. Many a times, these trenches are not filled back properly resulting in large permanent settlement in the pavement constructed above the trench. Geogrids have been used at the top of the base course to decrease the settlement. This article presents the observed settlements of unreinforced and geogrid reinforced pavement, monitored over a period of 12 months under the urban traffic load. Finite element (FE) analysis of the trench and the pavement, unreinforced and reinforced, under a transient pulse load is also carried out by using PLAXIS. It is observed that the vertical settlement can be greatly reduced by using geogrids in the pavement. The results obtained from case study and PLAXIS show that the geogrids improve the stiffness and strength of asphalt pavement and control the rut formation in the pavement.